Reflexiones en torno a la ley de la igualdad entre el hombre y la mujer en la sucesión de los títulos nobiliarios - de la Puente Ortas, Fco. Gerardo (REVISTA ESTUDIOS INSTITUCIONALES, 2016)
El presente artículo es una reflexión desde el punto de vista histórico-jurídico sobre la ley 33/2006 de 30 de octubre, sobre igualdad del hombre y la mujer en el orden de sucesion de los titulos nobiliarios. Law 33/2006 of 30 October, on equality of men and women in the order of succession of titles, is intended to promote equal rights and duties enshrined in our Constitution, but actually raises a conglomerate problems due to the existence of defects in your configuration. This study reveals the situation of men and women, while the law of processed, the handling process, the positions stated in parliamentary debates and an analysis of the deviations and the severity of the consequences thereof.